SOFT GAMMA REPEATERS AND ANOMALOUS X-RAY PULSARS BEYOND MAGNETARS - Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2016)
The observational properties of Soft Gamma Repeaters and Anomalous X-ray Pulsars (SGR/AXP) indicate to necessity of the energy source different from a rotational energy of a neutron star. The model, where the source of the energy is connected with a magnetic field dissipation in a highly magnetized neutron star (magnetar) is analyzed. Some observational inconsistencies are indicated for this interpretation. Slow rotating radiopulsars with very high magnetic fields were discovered, which don’t show any features of SGR, there are SGR/AXP in which an upper limit of the dipole magnetic field strength corresponds to average magnetic field of radio pulsars. The energy source, connected with the nuclear energy of superheavy nuclei stored in the nonequilibrium layer of low mass neutron star is discussed. The losses of rotational energy, observed in SGR/AXP are connected with a magnetised stellar wind, induced by the bursting events near the neutron star surface.